Evaluasi Sistem Pengendalian Intern Persediaan pada PT Pos Indonesia (Persero) Binjai 2023 - Dita Ananda Bangun; Muhammad Irwan Padli Nasution (Pusat Riset dan Inovasi Nasional, 2023)
Inventory is one of the important asset to be owned by company. Because of inventory is asset of company so the company should have a good internal control of inventory to keep them from many things bad that might happen. Therefore, the purpose of this research is to analysis internal control system that PT Pos Indonesia (Persero) Binjai has been done for get the description of activity internal control system of inventory in applied by that company. To get the needed data so writer use the data collector in the form of literature and interview. In this research, data type that used is primary and sekunder data. The writer get the data by interview and observation. The result in this research known internal control system of inventory in PT Pos Indonesia (Persero) Binjai is effective enough, where there is function division between in and out of goods. The monitoring of inventory also being done in periodical by logistic through the activities of post office’s goods stock.